Exploring nutritional status, physical activity and body mass index of Pakistani teens - Khan, Kiran; Jameel, Nazia; Khalil, Rehana; Gul, Saadia (International Journal of Research in Medical Sciences, 2017)
Background: Obesity is becoming an increasingly prevalent problem in Pakistan, as it has in other developing countries. Childhood obesity poses high cost to the well-being and negatively affects children’s health, causes chronic disease as children grow older. The aim of this study was to explore nutritional status, physical activity and body mass index (BMI) of school and college going students of mid and late adolescence age (14 to 19 years) studying in multi-ethnic city of Karachi, Pakistan. Methods: A descriptive cross-sectional study was carried out among school and college going students of public and private educational institutes of Karachi, Pakistan. The study sample of 171 students was conveniently selected from these institutes. The data was collected through a semi-structured questionnaire. In order to calculate BMI, the height and weight of each student were measured after completion of the questionnaire. The data were entered and analysed using IBM SPSS version for Windows 20.0 software. Results: The average age of the respondents was 16.2 years with 68% students belonged to school and 32% to College, and 57.3% were males and 42.7% were females. More than half sample (59.6%) participants belonged to privileged and 40.4% to underprivileged class. The sample was eating a wide variety of junk food in daily routine including chips, packed fruit juices, packed flavoured milk, ice creams/ frozen yogurts both at home and at school/college. The physical activity of the school students was found to be better than the college students. No participant had regular activity or strenuous physical games for more than one hour per day. Around one third (38%) respondents used to watch TV or play computer games for more than two hours a day. Almost half of the students’ BMI was within the normal ranges, but remaining half of the sample was either overweight or underweight. Conclusions: This study indicates that a large proportion of school and college students had physical inactivity, unhealthy dietary habits and they were overweight. All these interrelated factors were independent of their household socioeconomic condition and ethnicity. There is a need to educate and create awareness about healthy lifestyle among the adolescents and the community at large.